The Perceptual Ability to Identify Japanese Language Accent Patterns by Indonesian Learners - Najoan, Franky Reymond (JAPANEDU: Jurnal Pendidikan dan Pengajaran Bahasa Jepang, 2021)
Research on the acquisition of suprasegmental sounds in Japanese has been carried out both in terms of production and perception. The conducted research shows that there are difficulties in acquiring Japanese sounds. This study focused on the perception of Japanese accents, with the aim of describing the learner’s ability to identify Japanese accent patterns. The data sources of this research are Japanese learners at beginner level. Data were collected using a test instrument, through a hearing test, in the form of a set of words which selected based on the category of words and patterns of Japanese accents to be measured by listening and recording techniques. The results showed that based on the results of the hearing test, of the 17 participants who completed the test reached the highest score 47.14 (S01), and the lowest score of 15.41 (S14), with an overall average score of 29.16 and Standard Deviation (SD) 7.9018. These scores represent the participants’ ability to identify Japanese accent patterns is in the very low category. The results indicate that the learners have difficulty identifying Japanese accent patterns. In fact, the vocabulary in research instrument was the basic vocabulary that had been learned by them. It can be concluded that the acquisition of vocabulary is not in line with the suprasegmental elements attached to these words. The results of this research need to be continued by applying listening exercises of Japanese accent.